Harnessing the Power of Hybrid Light Propagation Model for Three-Dimensional Optical Imaging in Cancer Detection - Wang, Lin; Zhu, Wentao; Zhang, Ying; Chen, Shangdong; Yang, Defu (Frontiers in Oncology, 2021)
Optical imaging is an emerging technology capable of qualitatively and quantitatively observing life processes at the cellular or molecular level, and plays a significant role in cancer detection. In particular, to overcome the disadvantages of traditional optical imaging that only two-dimensionally and qualitatively detect biomedical information, the corresponding three-dimensional (3D) imaging technology is intensively explored to provide 3D quantitative information, such as localization and distribution, and tumor cell volume etc. To retrieve these information, light propagation models that reflects the interaction between light and biological tissues are an important prerequisite and basis for 3D optical imaging. This review concentrates on the recent advances in hybrid light propagation models, with particular emphasis on their powerful use for 3D optical imaging in cancer detection. Finally, we prospect the wider application of hybrid light propagation model and future potential of 3D optical imaging in cancer detection.